Non‐cervical human papillomavirus‐related disease. (16th September 2013) - Lippiatt, Jonathan; Powell, Ned; Tristram, Amanda
<x xml:space="preserve">Abstract</x> Key content Human papillomavirus (HPV) is associated with neoplastic disease at sites other than the cervix. Cancer caused by HPV may behave differently to other cancers at the same site. The presence of HPV alone is not sufficient to demonstrate a causal association. HPV vaccination has the potential to impact on disease burden beyond cervical cancer. Learning objectives To understand the spectrum of disease caused by HPV. To review the management of HPV‐associated disease in pregnancy. To be aware that future research into HPV‐related disease may alter management. Ethical issues What advice should women be given regarding their sexual partners? Should boys be offered HPV vaccination?